Current Clinical Application of Artificial Intelligence in Medical Imaging - N. V. Nudnov; G. А. Pan’shin (Вестник рентгенологии и радиологии)
Artificial intelligence (AI) is currently developing very efficiently, and its applications are valuable in many fields of science, including medicine, mainly because of its ability to ensure accuracy, objectivity and automation, in particular, in the diagnostic process. Rapid development of diagnostic technologies provides an opportunity to introduce innovative solutions into modern medicine through the use of AI, which makes it possible to relieve medical workers by speeding up the diagnostic process and improving its quality as well as effectiveness of subsequent special treatment based on its results. This review briefly presents the current state of knowledge and a number of existing AI models applied in everyday practice in medical imaging. AI has great potential to transform X-ray diagnostics and other areas of medicine, especially in the analysis of medical images. Despite the difficulties associated with AI implementation in practice, such as the need for proper staff training and ethical issues, the advantages of its application are very significant. AI can help improve diagnostic accuracy, speed up the diagnostic process itself, and reduce medical costs. Further development of AI technologies combined with the constant cooperation between Russian AI developers and medical professionals will contribute to even greater advances in healthcare, which will undoubtedly benefit both patients and staff of medical institutions.